Ultramafic and Mafic Rocks of Thurly Gah and Their Relationship to the Chilas Complex, N. Pakistan - Khan, M. Asif; Habib, M.; Jan, M. Qasim (Journal of Himalayan Earth Sciences, 1985)
Detailed field and petrographic studies in Thurly area substantiate the idea of a two-fold subdivision of the Chilas Complex. Much of the area is occupied by the association of "Main Norites" with subordinate pyroxenites and anorthosites displaying only local layering. Apparently intrusive into these is the association of ultramafic-mafic rocks occurring principally in a 2.5 x 1 km lensoid body. There possess well-developed sedimentary features, especially layering, and comprise dunite, peridotites, pyroxenites, troctolite, norite, anorthosite, and olivine/pyroxene pegmatites. There are distinct differences in the mineralogy of the two associations, especially in the composition of plagioclase and oxide minerals. It is suggested that the ultramafic-mafic association was derived from a picritic magma emplaced in the floor of a crystalizing (main) noritic magma. There is a strong concordance in the planar structures of the two associations and the crystallization of the ultramafic-mafic rocks apparently preceded all deformational events.